Pseudorabies Virus-Induced Leukocyte Trafficking into the Rat Central Nervous System - Rassnick, Stefanie (American Society for Microbiology, 1998)
When the swine alphaherpesvirus pseudorabies virus (PRV) infects the rat retina, it replicates in retinal ganglion cells and invades the central nervous system (CNS) via anterograde transynaptic spread through axons in the optic nerve. Virus can also spread to the CNS via retrograde transport through the oculomotor nucleus that innervates extraocular muscles of the eye. Since retrograde infection of the CNS precedes anterograde transynaptic infection, the temporal sequence of infection of the CNS depends on the route of invasion. Thus, motor neurons are infected first (retrograde infection), followed by CNS neurons innervated by the optic nerve (anterograde transynaptic infection). This temporal separation in the appearance of virus in separate groups of neurons enabled us to compare the immune responses to different stages of CNS infection in the same animal. The data revealed focal trafficking of peripheral immune cells into areas of the CNS infected by retrograde or anterograde transport after PRV Becker was injected into the vitreous body of the eye. Cells expressing the leukocyte common antigen, CD45(+), entered the area of infection from local capillaries prior to any overt expression of neuropathology, and quantitative analysis demonstrated that the number of cells increased in proportion to the number of infected neurons within a given region. Recruitment of cells of monocyte/macrophage lineage began prior to the appearance of CD8(+) cytotoxic lymphocytes, which were, in turn, followed by CD4(+) lymphocytes. These data demonstrate that PRV replication in CNS neurons stimulates the focal infiltration of specific classes of CD45(+) cells in a time-dependent, temporally organized fashion that is correlated directly with the number of infected neurons and the time that a given region has been infected.